The Cumacea of the Red Sea and Gulf of Aden, with the description of four new species and one genus - Mühlenhardt-Siegel, Ute (Zootaxa, 2008)
Cumacea from benthos samples of the RV Meteor cruise 5/2 (1987) are investigated. Six species were identified. Descriptions of a new genus and species Paravaunthompsonia meteorae and three new species Pseudosympodomma adensis, Cyclaspis carinobacata (Bodotriidae) and Procampylaspis hildegardae (Nannastacidae) are given.